Noninvasive skin swab analysis detects environmental drug exposure of pharmacy staff - Samantha Thompson; Samvel Abelyan; Morgan Panitchpakdi; Jasmine Zemlin; Sydney Thomas; Haoqi Nina Zhao; Pieter C. Dorrestein; Shirley M. Tsunoda (Wiley, 2024)
Abstract The skin is complex with multiple layers serving protective, regulatory, and detective functions. The skin hosts chemicals originating from consumption, synthesis, and the environment. Skin chemicals can provide insight into one's daily routine or their level of safety in a work environment. The goal of this study was to investigate the utility of noninvasive skin swabs to detect drugs in a pharmacy setting and to determine whether drugs are transferred to the skin of pharmacy staff. To answer this question, skin swabs were collected from healthy pharmacy staff workers and healthy non‐pharmacy individuals and analyzed via untargeted liquid chromatography-tandem mass spectrometry (LC-MS/MS). Drugs were annotated through library matching against the GNPS community spectral library. We then used questionnaire data to exclude medications that participants took orally or applied topically and focused on the drugs participants were exposed to in the work setting. Overall, pharmacy staff had a higher number and variety of medications on their skin as compared with healthy individuals who did not work in a pharmacy. In addition, we identified some chemicals such as N,N‐Diethyl‐metatoluamide on a large number of subjects in both experimental and control groups, indicating environmental exposure to this compound may be ubiquitous and long‐lasting.